Foraging patterns of Antarctic minke whales in McMurdo Sound, Ross Sea. Issue 6 (December 2020) - Ainley, David G.; Joyce, Trevor W.; Saenz, Ben; Pitman, Robert L.; Durban, John W.; Ballard, Grant; Daly, Kendra; Kim, Stacy
Abstract: Evidence indicates that Antarctic minke whales (AMWs) in the Ross Sea affect the foraging behaviour, especially diet, of sympatric Adélie penguins (ADPEs) by, we hypothesize, influencing the availability of prey they have in common, mainly crystal krill. To further investigate this interaction, we undertook a study in McMurdo Sound during 2012–2013 and 2014–2015 using telemetry and biologging of whales and penguins, shore-based observations and quantification of the preyscape. The 3D distribution and density of prey were assessed using a remotely operated vehicle deployed along and to the interior of the fast-ice edge where AMWs and ADPEs focused their foraging. Acoustic surveys of prey and foraging behaviour of predators indicate that prey remained abundant under the fast ice, becoming successively available to air-breathing predators only as the fast ice retreated. Over both seasons, the ADPE diet included less krill and more Antarctic silverfish once AMWs became abundant, but the penguins' foraging behaviour (i.e. time spent foraging, dive depth, distance from colony) did not change. In addition, over time, krill abundance decreased in the upper water column near the ice edge, consistent with the hypothesis (and previously gathered information) that AMW and ADPE foraging contributed to an alteration of prey availability.